The early development of football
1 online resource.
Keywords: This fascinating collection brings together leading football historians and sociologists from the UK, Germany, the USA and Australia to offer fresh perspectives on the early development of football (soccer), not only illuminating our understanding of the early history of the world's most popular sport, but also the importance of sport in our broader social and cultural history. The book presents new evidence and fresh perspectiveswhich will inform the robust debate that has been raging about the origins and early development of football. It addresses key issues at the centre of this debate, including the influence of former English public schoolboys, the development of football subcultures outside of prestige educational institutions, and the intersection and divergence of the various football codes around the world. The Early Development of Football is an important resource for anyone working in the history of football or sports in general, football studies or the sociology of sport. It is also a useful read for those interested in sport management and the development of sports organisations and rules.